Deletion of mouse FXR gene disturbs multiple neurotransmitter systems and alters neurobehavior - Huang, Fei; Wang, Tingting; Lan, Yunyi; Yang, Li; Pan, Weihong; Zhu, Yonghui; Lv, Boyang; Wei, Yuting; Shi, Hailian; Wu, Hui; Zhang, Beibei; Wang, Jie; et al. (Frontiers in Behavioral Neuroscience, 2015)
Farnesoid X receptor (FXR) is a nuclear hormone receptor involved in bile acid synthesis and homeostasis. Dysfunction of FXR is involved in cholestasis and atherosclerosis. FXR is prevalent in liver, gallbladder, and intestine, but it is not yet clear whether it modulates neurobehavior. In the current study, we tested the hypothesis that mouse FXR deficiency affects a specific subset of neurotransmitters and results in a unique behavioral phenotype. The FXR knockout mice showed less depressive-like and anxiety-related behavior, but increased motor activity. They had impaired memory and reduced motor coordination. There were changes of glutamatergic, GABAergic, serotoninergic and norepinephrinergic neurotransmission in either hippocampus or cerebellum. FXR deletion decreased the amount of the GABA synthesis enzyme GAD65 in hippocampus but increased GABA transporter GAT1 in cerebral cortex. FXR deletion increased serum concentrations of many bile acids, including taurodehydrocholic acid, taurocholic acid, deoxycholic acid, glycocholic acid, tauro-α-muricholic acid, tauro-ω-muricholic acid, and hyodeoxycholic acid. There were also changes in brain concentrations of taurocholic acid, taurodehydrocholic acid, tauro-ω-muricholic acid, tauro-β-muricholic acid, deoxycholic acid, and lithocholic acid. Taken together, the results from studies with FXR knockout mice suggest that FXR contributes to the homeostasis of multiple neurotransmitter systems in different brain regions and modulates neurobehavior. The effect appears to be at least partially mediated by bile acids that are known to cross the blood-brain barrier inducing potential neurotoxicity.